Intramolecular OH⋅⋅⋅Fluorine Hydrogen Bonding in Saturated, Acyclic Fluorohydrins: The γ‐Fluoropropanol Motif. Issue 49 (23rd October 2015) - Linclau, Bruno; Peron, Florent; Bogdan, Elena; Wells, Neil; Wang, Zhong; Compain, Guillaume; Fontenelle, Clement Q.; Galland, Nicolas; Le Questel, Jean‐Yves; Graton, Jérôme
Abstract: Fluorination is commonly exercised in compound property optimization. However, the influence of fluorination on hydrogen‐bond (HB) properties of adjacent functional groups, as well as the HB‐accepting capacity of fluorine itself, is still not completely understood. Although the formation of OH⋅⋅⋅F intramolecular HBs (IMHBs) has been established for conformationally restricted fluorohydrins, such interaction in flexible compounds remained questionable. Herein is demonstrated for the first time—and in contrast to earlier reports—the occurrence of OH⋅⋅⋅F IMHBs in acyclic saturated γ‐fluorohydrins, even for the parent 3‐fluoropropan‐1‐ol. The relative stereochemistry is shown to have a crucial influence on the corresponding h1 J OH⋅⋅⋅F values, as illustrated by syn ‐ and anti‐ 4‐fluoropentan‐2‐ol (6.6 and 1.9 Hz). The magnitude of OH⋅⋅⋅F IMHBs and their strong dependence on the overall molecular conformational profile, fluorination motif, and alkyl substitution level, is rationalized by quantum chemical calculations. For a given alkyl chain, the "rule of shielding" applies to OH⋅⋅⋅F IMHB energies. Surprisingly, the predicted OH⋅⋅⋅F IMHB energies are only moderately weaker than these of the corresponding OH⋅⋅⋅OMe. These results provide new insights of the impact of fluorination of aliphatic alcohols, with attractive perspectives for rational drug design. Abstract : HB source : Intramolecular OH⋅⋅⋅fluorine hydrogen bonding in acyclic, saturated γ‐fluorohydrins is evidenced by the presence of h1 J OH⋅⋅⋅F coupling constants (up to 6.6 Hz at 25 °C). A thorough analysis of the fluorohydrin conformational profile and the OH⋅⋅⋅F intramolecular hydrogen‐bond energies is fully consistent with experimental NMR data and provides insight into the competing stabilizing and repulsive interactions that determine the extent of intramolecular hydrogen bonding.